Relationship between metacognitive skills and critical thinking in elementary science lectures through guided inquiry model - Anindita SHM Kusuma; Ahmad Busyairi (Jurnal Pijar Mipa, 2023)
Learning science helps one develop understanding and thinking habits and allows students to master many life skills. Science learning emphasizes empowering high-level thinking skills such as metacognitive and critical thinking. This study aimed to determine the relationship between metacognitive skills and critical thinking using a guided inquiry strategy in elementary science education lectures. The study results show a relationship between metacognitive skills and students' critical thinking in Elementary Science Education lectures in learning using the guided inquiry strategy. The value of the correlation coefficient (r) of students' metacognitive skills with critical thinking in Elementary Science Education lectures is 0.859 (very high). The direction of the relationship between metacognitive skills and critical thinking is a positive relationship. The coefficient of determination (r2) is 0.737, so it can be explained that the variability of students' critical thinking values is determined by 73.3% of metacognitive skills. The regression significance value proves that the regression line equation can be used for prediction. The equation of the regression line for the relationship between metacognitive skills and students' critical thinking in Elementary Science Education lectures using the guided inquiry strategy is Y ̂=0.960+0.863X.